Minimizing Deterministic Timed Finite State Machines. Issue 7 (2018) - Bresolin, Davide; Tvardovskii, Aleksandr; Yevtushenko, Nina; Villa, Tiziano; Gromov, Maxim
Abstract: Timed automata and timed finite state machins (TFSMs) have been proposed to represent more accurately the behaviour of systems in continuous time. Recently, we introduced a model of TFSMs that extends the expressive power of FSMs by introducing a single clock, timed guards which restrict when the input/output transitions may happen, and timeouts on the transitions. We derived an abstraction procedure to convert a TFSM into an equivalent untimed FSM. Here, we extend the model with output timeouts and derive a minimal form for deterministic TFSMs that reduces the number of states, the number of transitions and the timeout values at each state.